Effect of chronic alcoholism on morphology and cell proliferation in salivary glands of Wistar rats (Research, Society and Development, 2022)
Several disorders which affect the oral cavity, salivary composition and, flow have been described in alcoholics chronic, thus this study aimed to evaluate the effects of chronic alcoholism on the salivary glands of Wistar rats. It was used 18 animals randomly subdivided into two groups: control (C) and treated with ethanol (T). C group (n=9) received water ad libitum and T group (n=9) received alcoholic solution ad libitum: 5% ethanol (1st week), 10% ethanol (2nd week) and 20% ethanol (for 9 weeks). After the treatment period, the animals were anesthetized and euthanized by decapitation. The parotid, submandibular and sublingual salivary glands of both groups were dissected, fixed and processed for paraffin. Histological sections were stained with hematoxylin/eosin and Picro-Sirius red stained, and the rate of cell proliferation was determined by immunohistochemistry with the marker KI-67. The salivary glands of group C showed preserved parenchyma, while the parotid and submandibular glands of group T showed hydropic degeneration, atypical nuclei, non-evident nucleolus and condensed chromatin in serous acini. The intercalated, striated and excretory ducts were seen with punctual areas of degeneration and nuclear atypia. In the submandibular glands there was a 73% increase in proliferative cells in T, when compared to C (p